TEST ASSESSMENT OF THE DEVELOPMENT OF KICKBOXERS COORDINATION ABILITIES OF AT THE STAGE OF SPORTMANSHIP IMPROVEMENT - Grahov, I.A.; Zebzeev, V.V.; Zdanovich, O.S.; Chernova, G.M. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop a set of methods for assessing the development of kickboxers’ coordination abilities at the stage of improving sportsmanship. Methods and structure of the study. In the experiment, methods of analysis and generalization of data from scientific and methodological literature and practical experience of trainers of the Fortuna sports and recreation center in Chaikovsky (Perm Territory) were used. Results and conclusions. The composition of the innovative complex of methods for assessing the development of coordination abilities included the following control exercises: striking with hands and feet on a scoreboard with numbers (kinesthetic differentiation), performing technical and tactical actions in time with a metronome (rhythmic abilities), passing stations with performing technical and tactical actions without the participation of the visual analyzer (spatial orientation), performing technical and tactical actions on a conditioned signal (complex motor reaction), performing technical and tactical actions with a change in motor task (dexterity), performing technical and tactical actions in an unstable position (ability to maintain balance).